Poly(3-methylthiophene) thin films deposited electrochemically on QCMs for the sensing of volatile organic compounds - Öztürk, S.; Kösemen, A.; Şen Z.; Kılınç N.; Harbeck M. (MDPI AG, 2016)
Poly(3-methylthiophene) (PMeT) thin films were electrochemically deposited on quartz crystal microbalance QCM transducers to investigate their volatile organic compound (VOC) sensing properties depending on ambient conditions. Twelve different VOCs including alcohols, ketones, chlorinated compounds, amines, and the organosphosphate dimethyl methylphosphonate (DMMP) were used as analytes. The responses of the chemical sensors against DMMP were the highest among the tested analytes; thus, fabricated chemical sensors based on PMeT can be evaluated as potential candidates for selectively detecting DMMP. Generally, detection limits in the low ppm range could be achieved. The gas sensing measurements were recorded at various humid air conditions to investigate the effects of the humidity on the gas sensing properties. The sensing performance of the chemical sensors was slightly reduced in the presence of humidity in ambient conditions. While a decrease in sensitivity was observed for humidity levels up to 50% r.h., the sensitivity was nearly unaffected for higher humidity levels and a reliable detection of the VOCs and DMMP was possible with detection limits in the low ppm range. © 2016 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Chemical gas sensor; DMMP; Electrochemical deposition; Humid air; Poly(3-methylthiophene); QCM; VOCs